2004
DOI: 10.1111/j.1365-313x.2004.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

The potyvirus recessive resistance gene, sbm1, identifies a novel role for translation initiation factor eIF4E in cell‐to‐cell trafficking

Abstract: SummaryFrom the characterization of the recessive resistance gene, sbm1, in pea we have identified the eukaryotic translation initiation factor, eIF4E, as a susceptibility factor required for infection with the Potyvirus, Pea seedborne mosaic virus. A functional analysis of the mode of action of the product of the dominant allele revealed a novel function for eIF4E in its support for virus movement from cell-to-cell, in addition to its probable support for viral RNA translation, and hence replication. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
207
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(218 citation statements)
references
References 40 publications
5
207
0
6
Order By: Relevance
“…In plants, a number of alleles at the eIF4E locus conferring resistance against multiple viruses in the family Potyviridae and at least one virus in the family Tombusviridae have been discovered recently. These include pvr1 in pepper (Ruffel et al, 2002;Kang et al, 2005a), mo1 in lettuce (Nicaise et al, 2003), sbm1 in pea (Gao et al, 2004), pot-1 in tomato (Ruffel et al, 2005), rym4/5 in barley (Stein et al, 2005), and nsv in melon (Nieto et al, 2006). It is striking to note that the critical amino acid substitution in eIF4E-pvr1, G107R, also exists at the homologous sites in several other recessive resistance genes: mo1 and sbm1 in lettuce and pea, respectively.…”
Section: The G107r Change Conferring Potyvirus Resistance Has Evolvedmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, a number of alleles at the eIF4E locus conferring resistance against multiple viruses in the family Potyviridae and at least one virus in the family Tombusviridae have been discovered recently. These include pvr1 in pepper (Ruffel et al, 2002;Kang et al, 2005a), mo1 in lettuce (Nicaise et al, 2003), sbm1 in pea (Gao et al, 2004), pot-1 in tomato (Ruffel et al, 2005), rym4/5 in barley (Stein et al, 2005), and nsv in melon (Nieto et al, 2006). It is striking to note that the critical amino acid substitution in eIF4E-pvr1, G107R, also exists at the homologous sites in several other recessive resistance genes: mo1 and sbm1 in lettuce and pea, respectively.…”
Section: The G107r Change Conferring Potyvirus Resistance Has Evolvedmentioning
confidence: 99%
“…It has been noted that the eIF4E proteins encoded by the pvr1 allele from pepper and the sbm1 allele from pea, which both contain the G107R substitution, show reduced cap binding (Gao et al, 2004;Kang et al, 2005a). Recent studies have suggested that the mRNA cap structure and potyvirus VPg at least partially share the protein binding pocket structure of the eIF4E protein or its isoform eIF(iso)4E (Michon et al, 2006;Miyoshi et al, 2006).…”
Section: The Vpg Binding and Cap Binding Abilities Of Eif4e Are Strucmentioning
confidence: 99%
See 1 more Smart Citation
“…One such example is the eIF4E gene that has been found to be associated with virus resistance in many plant species (Nicaise et al 2003;Gao et al 2004;Yoshii et al 2004;Kang et al 2005;Kanyuka et al 2005;Stein et al 2005;Nieto et al 2006Nieto et al , 2007Ibiza et al 2010;Naderpour et al 2010;Piron et al 2010), including resistance to potato virus Y in potato, tomato, and pepper (Ruffel et al 2002(Ruffel et al , 2005Cavatorta et al 2011;Duan et al 2012). Variants of eIF4E confer resistance to PVY in the potato wild species relatives S. chacoense, S. demissum, and S. etuberosum , permitting the eventual use of this gene in future biotech potato varieties.…”
Section: Resistance To Biotic and Abiotic Stressesmentioning
confidence: 99%
“…Recently, a potential link between virus accumulation and cell-to-cell movement was identified when the eukaryotic translocation factors eIF4E and eIF(iso)4E were shown to aid in virus cell-to-cell movement (Gao et al 2004). These observations correspond with earlier studies where plant mutants with eIF4E exhibit limited virus spread (Arroyo et al 1996).…”
Section: Potyviruses Components Of Transport Networkmentioning
confidence: 99%